Clinical and Genetic Heterogeneity in Six Tunisian Families With Horizontal Gaze Palsy With Progressive Scoliosis: A Retrospective Study of 13 Cases - Bouchoucha, Sami; Chikhaoui, Asma; Najjar, Dorra; Dallali, Hamza; Khammessi, Maleke; Abdelhak, Sonia; Nessibe, Nabil; Shboul, Mohammad; Kircher, Susanne G.; Al Kaissi, Ali; Yacoub-Youssef, Houda (Frontiers in Pediatrics, 2020)
Background: Horizontal gaze palsy with progressive scoliosis (HGPPS) is a rare autosomal recessive congenital disorder characterized by absence of conjugate horizontal eye movements, and progressive debilitating scoliosis during childhood and adolescence. HGPPS is associated with mutations of the ROBO3 gene. In this study, the objective was to identify pathogenic variants in a cohort of Tunisian patients with HGPPS and to further define ROBO3 genotype-phenotype correlations. Methods: Thirteen Tunisian patients from six unrelated consanguineous families manifested HGPPS were clinically and genetically investigated. We searched for the causative variants for HGPPS using Sanger sequencing and whole exome analysis. Results: Four distinct homozygous mutations were identified in ROBO3 gene. Two of these mutations were newly identified homozygous and nonsynonymous, predicted as damaging to protein by in silico analysis. The other two mutations were previously reported in Tunisian patients with HGPPS. Mutations were validated by Sanger sequencing parents and affected individuals. Conclusion: To the best of our knowledge, this is the first largest cohort of Tunisian families with HGPPS in whom ROBO3 mutations were identified. These molecular findings expand our knowledge of the ROBO3 mutational spectrum, which could have importance for medical team proper management of the disease and allows accurate genetic counselling to prevent the reoccurrence of HGPPS in families with history of this disease.